Evaluation of deterioration of library materials at Olabisi Onabanjo university library, Ago-Iwoye, Nigeria (2005)
The nature and extent of deterioration of four categories of library materials (newsprints, textbooks, dissertations and journals) at Olabisi Onabanjo University Library, Ago-Iwoye, Ogun State, Nigeria was investigated. The pH, fold endurance and the extent of mutilation were determined, while the microorganisms associated with decomposing library materials were isolated and identified. The library materials with acidic papers constituted 69.0% for textbooks, 52.2% for journals, 73.2% for dissertations and 85.3% for newspapers. About 93% of textbooks, 98% of journals and 89% of dissertations did not break up to six folds. The percentage of mutilated books was 11.9% for textbooks, 5.7% for journals and 10.4% for dissertations. The microorganisms associated with deteriorating library materials were Bacillus sp., Streptococcus sp. Staphylococcus sp., Pseudomonas sp. and Flavobacterhcm sp. for bacteria, while the moulds included Aspergillus niger, Aspergillus flavus, Aspergillus fumigatus, Penicillium sp., Cladosporium sp., Neurospora sp, Penicillium sp and Rhizopus sp. The ability of these microorganisms to degrade (utilise) native cellulose (filter papers) was investigated so as to be able to know whether these organisms could actually deteriorate papers. All the moulds except Neurospora sp. effectively utilised filter papers than the two bacterial species Bacillus sp. and Pseudomonas sp. that also degraded filter papers. A. niger and A. flavus most utilised the filter papers for growth among the moulds. Apart from the deteriorative effect, the health implications of the presence of microorganisms particularly the moulds on library materials to library users are discussed.